The Labour Market Situation of Population Groups in the Visegrád Countries - Łukasz Arendt; Leszek Kucharski; Iwona Kukulak‑Dolata; Anna Rutkowska (Comparative Economic Research)
The paper presents the results of an analysis of selected population groups in the labour markets of the Visegrád Group (V4) countries (i.e., Czechia, Hungary, Poland and Slovakia) from 2015 to 2020. The study assesses the relative situation of these groups, taking into account the skill profiles of their members. Thus, we identify groups with the relatively best and worst employability prospects in the V4 labour markets. To this end, the parameters of a polynomial logit model (representing relative risk ratios for exiting employment or unemployment) are estimated. The study reveals that in all V4 countries, tertiary graduates were in the best position in the labour markets. The highest‑skilled professionals had the best chances of finding a job while being the least likely to become unemployed. The most uncertain labour market situation concerned people aged up to 24 years, the least‑educated and low‑skilled people, and people aged 55 years and older. This points to the need to provide support programmes targeted at these social groups, implemented within the public policies, i.e., labour market and educational policies, with special emphasis on the adult learning system. The main contribution of the study is that it includes the task‑content approach to analyse the employability prospects in the V4 labour markets.